729 The impact of immune and targeted therapies for melanoma in asian populations: a national cancer database analysis 2004–2016. (9th November 2020) - Cao, Lifen; Sugumar, Kavin; Mangla, Ankit; Miller, Megan; Rothermel, Luke
Abstract : Background: Immune checkpoint inhibitors (ICI) and targeted therapies (TT) have improved the survival outcomes in patients with advanced melanoma. However, less is known about their impact on Asian patients with melanoma. In this study, we hypothesize that patients of Asian ancestry would have improved survival for advanced melanoma since the introduction of ICI and TT in 2011. Methods: Asian patients with melanoma were identified in the National Cancer Database (NCDB) from 2004–2016. Patient, tumor, and treatment characteristics were compared for populations treated before and after 2011 using Chi-square analyses. Overall survival (OS) was analyzed using Kaplan-Meier estimates. Results: 1, 411 Asian patients with melanoma were identified. Overall, 21% were melanoma in situ, and 79% were invasive melanomas. 62% of patients did not have a documented histologic subtype. The most common reported histologies were superficial spreading (14%) and acral lentiginous (10%) melanomas. Primary locations included 41% lower extremity, 17% upper extremity, and 11% head and neck. The age at diagnosis has increased during the study period - 38% over 60 years old in 2004, to 54% in 2016 (P<0.002). Kaplan-Meier survival estimates were performed for the whole Asian melanoma population and showed worse OS for all patients diagnosed after 2011 compared with patients diagnosed before 2011 - 83% vs 84% at 24 months (P=0.0033), 71% vs 76% at 48 months (P<0.001), respectively. However, the OS for those stage IV melanomas diagnosed after 2011 is better compared to patients diagnosed before 2011 - 52% vs. 26% at 24 months (P<0.001), and 20% vs. 13% at 48 months (P<0.001), respectively. (table 1) The worse OS trend seen for all patients was driven by those with early stage disease and likely does not reflect melanoma specific survival. Utilization rates of ICI and TT in Stage IV melanoma in Asian populations was significantly higher after 2011 (9% versus 30% before and after 2011 respectively, p=0.026). This was comparable to the utilization rates of 12% vs 34% for all patients (all races) with stage IV melanomas captured in the NCDB for the periods from 2004–2011 and 2012–2016. Conclusions: Asian patients with melanoma are receiving diagnoses at older ages. Despite decreases in OS for all Asian patients with melanoma, advanced stage IV of the diseases have improved outcomes for the group treated in the era of ICI and TT. Further investigation is warranted to understand the treatment, patient, and tumor characteristics that predict response in this demographic of patients.